Evaluation of fodder plants (Ficus polita, Azadirachta indica and Vernonia amygdalina) for their phytochemical and antibacterial properties - Festus Temitope Ajayi; Sunday Oloruntoba Omotoso; Joseph Oluwafemi Odejide (Cogent Food & Agriculture, 2016)
In Nigeria, fodder plants are important components of ruminant feeding systems. The wide arrays of secondary metabolites in them are potential source of antibacterial materials; if harnessed, could serve as alternative to conventional antibiotics. This study was designed to evaluate the phytochemical and antibacterial properties of acetone and ethanol extracts of Ficus polita, Azadirachta indica, and Vernonia amygdalina leaves against selected bacterial species by Agar well diffusion and broth micro dilution methods. Phytochemical screening showed that concentration of phytochemicals differed significantly (p < 0.05) among the leaf extracts. Alkaloids (13.04–15.74 mg/100 g) were highest in all the fodder plants. All the leaf extracts were more effective against Staphylococcus aureus and Pseudomonas aeruginosa with zone of inhibition ranging from 12.06–28.00 mm and 10.50–23.00 mm respectively. In terms of sensitivity, the reference antibiotic (gentamycin) showed more activity against Escherichia coli and Salmonella typhi than leaf extracts. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values ranged from 0.14 to 0.35 mg/mL and 0.60 to 1.90 mg/mL respectively. The lower range of MIC and MBC values translates to high antibacterial potency of the plant extracts; an indication of broad spectrum of activity against all the tested bacterial species.